Cost of delivering childhood RSV prevention interventions to the health system in Kenya: a prospective analysis - Ranju Baral; Clint Pecenka; Rose E Jalang'o; Elkanah Otiang; Joseph Odiyo; Bryan O Nyawanda; Joyce U Nyiro; Patrick Munywoki (BMJ Open)
Objectives To evaluate the cost of delivering childhood respiratory syncytial virus (RSV) prevention interventions to the health system in Kenya.Design A prospective (cost projection) activity-based costing study.Setting Kenya, national introduction of interventions.Participants Not applicable.Interventions A single-dose RSV maternal vaccine and a single-dose, long-acting monoclonal antibody (mAb).Primary and secondary outcome measures Cost per eligible target population; cost per dose administered; non-commodity cost of delivery. Costs are reported in 2023 USD.Results RSV interventions are expected to be delivered using existing systems: maternal vaccine using the antenatal care platform and the mAb delivered similar to existing birth dose vaccines. Assuming a price of US$3 per dose (for both interventions) and baseline coverage rates averaging 50% for the maternal vaccine and 86% for the mAb, the estimated cost of delivering maternal vaccine was US$1.74 (financial) and US$6.60 (economic) per vaccinated woman, and the cost of delivering mAbs was US$1.56 (financial) and US$6.27 (economic) per vaccinated child. Excluding commodity cost, the cost of delivering maternal vaccine was US$1.32 (financial) and US$2.72 (economic) and that for mAb was US$1.23 (financial) and US$2.48 (economic). Cost differences between the two interventions are driven by the anticipated baseline coverage. Health worker training, service delivery and programme planning and coordination were major cost drivers.Conclusion This study presents the prospective cost of new RSV intervention introduction and delivery in low-income and middle-income country settings, which is largely unknown. Cost estimates incorporate anticipated health system strengthening activities needed to deliver the future RSV interventions. These cost estimates support country-level and global-level decision-makers evaluating implementation feasibility and intervention affordability.